Evidence for deformation twinning of the D019-α2 phase in a high Nb containing TiAl alloy. (June 2019) - Song, Lin; Wang, Li; Oehring, Michael; Hu, Xingguo; Appel, Fritz; Lorenz, Uwe; Pyczak, Florian; Zhang, Tiebang
Abstract: It is commonly agreed that the α2 phase in γ(TiAl)-based alloys is quite difficult to deform plastically especially by order twinning. In the present study, for the first time we report deformation twinning in the α2 phase in a nearly-lamellar two-phase γ-TiAl alloy investigated by electron microscopy. Diffraction pattern and high-resolution images indicate that the twinning plane is ( 20 2 ¯ 1 ) and the twinning direction is [ 10 14 ¯ ], which is essentially analogous to what has been observed in disordered hexagonal structures. The twinning and anti-twinning mechanisms are interpreted. The twinning is a combined result of superpartial dislocation glide activated by the dissociation of <2 c + a > type superdislocation, accompanied by atomic shuffling and short-range diffusion which is facilitated by the anti-structural bridges diffusion mechanism during high-temperature compression. The appearance of deformation twinning in the α2 phase can play an important role for the excellent mechanical properties of high Nb containing TiAl alloys, which is of great importance for the further development of γ-TiAl alloys. Highlights: Deformation twinning of α2 phase is firstly observed in a two-phase γ-TiAl alloy. The twinning system is similar to that observed in disordered α structure. Twinning and anti-twinning elements are revealed. Atomic shuffling and short-range diffusion are responsible for deformation twins.